Utjecaj radijalnog i aksijalnog razrmaka na emitiranu buku i performance ventilatora - Čudina, Mirko (Promet - Traffic&Transportation)
Among all auxilimy units of the air cooled diesel engine acooling fan is the noisiest. One of the noise generation mechanismsis the blade interaction with the vortices occurring in theradial and axial clearances of the fan due to the pressure differencebetween the pressure and suction side of the rotorblade. This mechanism of noise generation is especially distinctif the fan is operating in a heavily loaded condition, i.e.,at partial flow rate, when the pressure differences are greater._In this paper the effects of radial and axial clearances betweenthe rotor and stator of the fan on the emitted noise and performances of the fan will be presented and discussed. The experimentalresults have shown that the radial and axial clearancehave its optimum with regard to the best value of emittednoise, performances, dimensions and technology of productionof the fan.